ANTIMICROBIOLOGICAL COMPOUNDS – A REVIEW - Dr. Priyambada Singh , Ms. Laiba Arsi, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Antimicrobiological compounds represent one of the greatest scientific breakthroughsin modern medicine and biotechnology, with profound applications across healthcare, veterinarypractice, agriculture, and industry. These compounds include antibiotics, antifungals,